Genetics of inflammatory bowel disease: from bench to bedside? - Satsangi, J (Taylor and Francis, 2001)
Epidemiological data, particularly concordance rates in twin pairs and in multiply affected families, provide strong evidence that both genetic and environmental influences are important in the development of the chronic intestinal inflammation characteristic of Crohn disease and ulcerative colitis. Furthermore, supplementary data now suggest that not only susceptibility, but also disease behavior and response to therapy may have a strong genetic influence. The model of disease susceptibility most pertinent to the inflammatory bowel diseases is that Crohn disease and ulcerative colitis are related polygenic disorders. Recently, this model has received strong support from the results of genome-wide scanning and candidate gene studies carried out in European, North American and Australian populations. In spite of all potential difficulties related to disease and ethnic heterogeneity, consistent replication of linkage has been found with distinct regions on chromosomes 16, 12, 6 (the major histocompatibility complex) and most recently chromosome 14. Whereas the linkages on chromosome 16 and 14 appear strongest in Crohn disease, the chromosome 12 locus appears most pertinent to ulcerative colitis, and the HLA region appears more pertinent in all forms of inflammatory bowel disease. The current challenge is to narrow these regions of linkage and identify the susceptibility genes within the regions. The task may be greatly benefited by the recent successful sequence data available from the human genome project. Compelling data have emerged to suggest genetic markers that may allow prediction of disease severity, and efficacy and tolerability of immuno-suppressants commonly used in inflammatory bowel disease.